2016
DOI: 10.1038/srep27988
|View full text |Cite
|
Sign up to set email alerts
|

Multi-class texture analysis in colorectal cancer histology

Abstract: Automatic recognition of different tissue types in histological images is an essential part in the digital pathology toolbox. Texture analysis is commonly used to address this problem; mainly in the context of estimating the tumour/stroma ratio on histological samples. However, although histological images typically contain more than two tissue types, only few studies have addressed the multi-class problem. For colorectal cancer, one of the most prevalent tumour types, there are in fact no published results on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
277
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(320 citation statements)
references
References 48 publications
1
277
4
Order By: Relevance
“…Therefore, we speculated that the classification performance could be improved by comprehensive involvement of multiple features. Combined feature analysis have been used in colorectal cancer histology [38]. We used each of the single parameters and trained an SVM classifier to identify control and two stages of SCR.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we speculated that the classification performance could be improved by comprehensive involvement of multiple features. Combined feature analysis have been used in colorectal cancer histology [38]. We used each of the single parameters and trained an SVM classifier to identify control and two stages of SCR.…”
Section: Classificationmentioning
confidence: 99%
“…For both types of classification, we quantitatively compared the performance of three classifiers. Discriminant analysis and KNN are two most common and basic machine learning algorithms [30,31,38,39]. We wanted to compare these basic algorithms to SVM which is known to be robust for small data set, and has been a widely used algorithm in other research fields [31,39].…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, image intensity or color histograms are not sufficient to discriminate between images, specially in case of Hematoxylin and Eosin (H&E) histo-pathological tissue images. In [157] it was demonstrated that texture features can efficiently discriminate between different tissue types. Also in case of differentiating between military camouflage uniform patterns or discriminating between military and civil vehicles, texture patterns play a key role.…”
Section: Image Featurementioning
confidence: 99%
“…For example, in differentiation between malignant and benign tumor, often the smoothness of the nuclei are taken into account [159]. While in other applications there different types to tissues are required to be classified [160] based on their textural patterns to determine cellular composition.For example, in Fig. 5.3 (e) and (f), the samples from a colorectal tissue image dataset, the saliency maps make the structural characteristics of the images more prominent.…”
Section: Application To Tissue Image Classificationmentioning
confidence: 99%